A framework for micropayment evaluation - Carsten Schmidt; Rudolf Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Lacking payment systems become a bottleneck for the vision of the Information Economy. In many cases payments of fractions of a cent, so-called micropayments, are of particular interest. In this paper we propose a framework to evaluate payment systems. The framework consists of a well structured parameter vector of desired attributes. For the evaluation of attribute values we suggest to use VTS diagrams from object oriented analysis and design. The framework is applied to DigiCash, SET and First Virtual.
urn:nbn:de:kobv:11-10060082
Keywords: 330; micropayments; electronic commerce